Investigation on Smoke Suppression Mechanism of Hydrated Lime in Asphalt Combustion - Kai Zhu; Yunhe Wang; Qi Zhou; Daquan Tang; Lingzhu Gu; Ke Wu (Journal of Chemistry)
In this study, cone calorimeter and thermogravimetric analyses were used to simulate the asphalt combustion process under the conditions of fire radiation and programmed temperature increase. The gaseous compositions and release rules were analyzed by infrared spectroscopy to investigate the influence of hydrated lime on the smoke suppression mechanism in the asphalt combustion process. The experimental results show that hydrated lime can promote the asphalt mastic surface to form a barrier layer during the combustion process. This barrier layer can reduce the burning intensity of asphalt. Although the compositions of gaseous products do not change much, the rates of CO production and smoke release are decreased. In addition, hydrated lime is alkaline and can thus neutralize acidic gases such as SO2 and reduce the toxicity of gaseous products. With the addition of 40 wt.% hydrated lime, the total smoke release and the CO release rate both decrease by more than 20% relative to the addition of the same amount of limestone fillers and decrease by more than 10% relative to the addition of the same amount of magnesium hydroxide flame retardant.